THE INFLUENCE OF THE COMPOUND EXERCISE "DOUBLE DUPLEX" ON SEVERAL FUNDAMENTAL FOOTBALL ACTIVITIES FOR SAMARAA PLAYERS - Lect. Asst. Ahmed Taha Ahmed (Proximus Journal Publishing, 2024)
The aims of research are: • To know the effect of double duplex on improving the basic skills of the footballer. • To determine how the double duplex affects the competitiveness of the footballer and improve their skills. • To determine the factors that influenced the successful use of double duplex, criticize its effectiveness on the player, and strengthen their competition. The research sample included 26 players from the Samaraa Sport Club in the youth category who officially registered with the Central Iraqi Football Federation for the 2023–2024 sports season, excluding goalkeepers from the test.
Keywords: compound exercises; dribbling; dodge